Vocational education and training in the Netherlands : short description - (:unkn) unknown (Publications Office of the European Union, 2016)
This overview of the vocational education and training (VET) system in the Netherlands is published during the Dutch Presidency of the Council of the EU (first half of 2016). It provides an insight into the main features of the Dutch VET system and highlights recent VET policy developments. "VET in the Netherlands is comprehensive and flexible and has good labour market outcomes. The Dutch experience shows that an effective VET system requires regular adjustments to keep meeting labour market and society needs. Striking a good balance between the system's accessibility, quality and efficiency is a constant challenge. In recent years, policies have focused on reducing early leaving from education and training and streamlining qualifications. Recent policies aim at increasing quality and efficiency by reducing programme duration and by strengthening performance-based funding. These and other measures benefit from a tradition of evidence-informed policy and practice." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; G 1.2 Arbeitsmarkt; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; L 6.2 Qualitätsmanagement/Qualitätssicherung; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Arbeitsmarkt; Früherkennung; Curriculumentwicklung; Anrechnung von Bildungsleistungen; Qualitätssicherung; Niederlande